Dysphagia in myasthenia gravis: the tip of the Iceberg - Umay, Ebru Karaca; Karaahmet, Fatih; Gurcay, Eda; Balli, Fatma; Ozturk, Erhan; Karaahmet, Ozgur; Eren, Yasemin; Ceylan, Tijen (Acta neurologica Belgica, 2018)
We evaluated swallowing function in patients with myasthenia gravis (MG) with or without dysphagia symptoms using different evaluation parameters and compared the results with those of healthy subjects. A total of 36 patients with MG and 25 healthy volunteers were included in the study. The subjects were classified into three groups; patients without dysphagia (group 1), patients with dysphagia (group 2), and healthy participants (group 3). The presence and severity of dysphagia, the oropharyngeal, pharyngeal, pharyngoesophageal, and esophageal phases were assessed using a screening test, manometric test, electrophysiologic studies [electroneuromyography (EMG)], fiberoptic endoscopic evaluation of swallowing (FEES), and barium swallow pharyngeal esophagography (BSPE), respectively. There was a significant difference between group 1 and group 3 in terms of BSPE ( p = 0.001) and manometry tests ( p = 0.001). A significant difference was found in all methods between group 2 and group 3 ( p = 0.001, for all). In the comparison of the patient groups, although the number of patients with dysphagia in group 2 was significantly higher in the clinical tests ( p = 0.007), FEES ( p = 0.001), and EMG ( p = 0.043) than in group 1, no difference was detected for BSPE ( p = 0.119) and manometry ( p = 0.644). Swallowing functions in patients with MG may be affected even without symptoms. This condition should be considered in their follow-up.